AN EXAMPLE OF SEQUENCE OF BLASCHKE PRODUCTS WHICH CONVERGE UNIFORMLY AT A UNIT DISC - Nastovski, Ljupčo (Matematichki Bilten, 2002)
The question of existence of sequence of Blaschke products which uniformly converges on the whole unit disk \(D=\{z:|z|